Southeast Asian Influence on Public International Law: State Practices and Implications - Subandi, Agit Yogi Subandi; Asnawi, Sona Asnawi; Mirza, Isroni Muhammad Miraj Mirza (International Law Discourse in Southeast Asia, 2025)
Southeast Asia, a region characterized by diverse legal traditions, political systems, and cultural practices, plays an important but often underappreciated role in the development and interpretation of public international law. This article examines the multifaceted influence of Southeast Asian states' practices on international legal norms and frameworks, answering three fundamental research questions: (1) How do state practices in Southeast Asian countries influence the development and interpretation of public international law? (2) What are the implications of Southeast Asian state practices for the application of and compliance with international law in the region? (3) How do Southeast Asian countries’ diplomatic strategies and international relations shape their contributions to public international law? By analyzing case studies and specific instances in which Southeast Asian legal norms have influenced international treaties, customary law, and general legal principles, this article highlights Southeast Asia’s active participation in the global legal arena. The study highlights the region’s potential to shape international legal norms through its unique legal traditions, enforcement practices, and diplomatic strategies. Ultimately, this research aims to advance understanding of Southeast Asia’s role in the international legal system and promote greater recognition of its influence in shaping global legal norms.